POWER BI AS A DATA VISUALIZATION AND ANALYSIS TOOL IN THE DEPARTMENT’S EDUCATIONAL MANAGEMENT - Kamalova, G.B.; Turashova, Sh.P.; Alimbay, A.M.; Nauryzbayev, D.B; Amangeldin, A.A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2026)
The article is devoted to the problem of increasing the efficiency of management of the university department through the introduction of business intelligence (BI) tools. Traditional methods of data analysis are time-consuming and do not allow for prompt management decisions in a modern educational environment characterized by a large amount of data. The purpose of this study is to substantiate the feasibility of using MS Power BI, one of the most popular business intelligence tools, to optimize the management of the university’s department, develop interactive dashboards for monitoring and visualizing key performance indicators of the department (faculty publication activity, student academic performance, etc.) in real time and assess their impact on improving management efficiency. activities of the department. The methodological basis of the research is a systematic approach, which uses a set of theoretical and experimental methods. To assess the impact of using Power BI on improving the effectiveness of department management, an experimental method of single-group preliminary and subsequent questionnaires was chosen. The sample consisted of 47 teachers of the Department of Informatics and Informatization of Education of the Kazakh National Pedagogical University named after Abai, 40% of whom have permanent general departmental duties. The survey was conducted in an online format using the GoogleForms service. The developed questionnaire included 21 questions on a 5-point Likert scale. The reliability of the results was confirmed using the Cronbach’s alpha coefficient. The results of the study. The proposed innovative method of department management based on Power BI has proven to be highly effective. It allows you to automate the generation of reports, quickly identify problem areas and trends, which, in turn, contributes to making informed management decisions. The results of the research have practical significance and will serve as a basis for implementation in the practice of department management in other educational institutions, contributing to the development of the educational management system.